Functional replacement of genes for individual polyketide synthase components in Streptomyces coelicolor A3(2) by heterologous genes from a different polyketide pathway. - Sherman, D H (1992)
Streptomyces coelicolor A3(2) and Streptomyces violaceoruber Tü22 produce the antibiotics actinorhodin and granaticin, respectively. Both the aglycone of granaticin and the half-molecule of actinorhodin are derived from one acetyl coenzyme A starter unit and seven malonyl coenzyme A extender units via the polyketide pathway to produce benzoisochromane quinone moieties with identical structures (except for the stereochemistry at two chiral centers). In S. coelicolor and S. violaceoruber, the type II polyketide synthase (PKS) is encoded by clusters of five and six genes, respectively. We complemented a series of S. coelicolor mutants (act) defective in different components of the PKS (actI for carbon chain assembly, actIII for ketoreduction, and actVII for cyclization-dehydration) by the corresponding genes (gra) from S. violaceoruber introduced in trans on low-copy-number plasmids. This procedure showed that four of the act PKS components could be replaced by a heterologous gra protein to give a functional PKS. The analysis also served to identify which of three candidate open reading frames (ORFs) in the actI region had been altered in each of a set of 13 actI mutants. It also proved that actI-ORF2 (whose putative protein product shows overall similarity to the beta-ketoacyl synthase encoded by actI-ORF1 but whose function is unclear) is essential for PKS function. Mutations in each of the four complemented act genes (actI-ORF1, actI-ORF2, actIII, and actVII) were cloned and sequenced, revealing a nonsense or frameshift mutation in each mutant.